Understanding perceived stigma and depression symptoms in maintenance hemodialysis patients: a network perspective - Li, Yurong; Yang, Yaoyao; Liang, Shiman; Cao, Guanghui; Yang, Jinjin (Frontiers in Psychology, 2025)
ObjectivesPatients undergoing maintenance hemodialysis (MHD) experience stigma due to their reliance on machines and changes in appearance, contributing to negative psychological outcomes. Depression symptoms can be considered a product of perceived stigma. However, the inter-relationships between perceived stigma and depression symptoms have not been examined using network analysis among MHD patients. The aim of this study was to model the perceived stigma and depression symptoms network structure, identify its core symptoms, analyze the internal connections between perceived stigma and depression symptoms, as well as identify bridge symptoms in the stigma-depression network.MethodsThis study included 301 MHD patients in a cross-sectional design. The participants completed self-reported measures of perceived stigma and depressive symptoms. A cross-sectional network analysis was performed using the R language to model the network structure and identify core and bridge symptoms in the network.ResultsThe core symptoms of perceived stigma from the network analysis were SIS5 “Feel others avoid me because of my illness” (Strength = 1.258, Betweenness = 32, Closeness = 0.00303), SIS13 “Feel others think I am to blame” (Strength = 1.142, Betweenness = 62, Closeness = 0.00298), and SIS11 “My job security has been affected” (Strength = 1.108, Betweenness = 72, Closeness = 0.00313). The core symptoms of depression were PHQ6 “Worthlessness” (Strength = 1.213, Betweenness = 13, Closeness = 0.00211), PHQ1 “Anhedonia” (Strength = 1.048, Betweenness = 20, Closeness = 0.0150), and PHQ2 “Sad mood” (Strength = 1.012, Betweenness = 8, Closeness = 0.0164). Regarding the combination network, results showed that SIS2 “Some people think I am less competent” (Bridge Strength = 0.917) and SIS11 “My job security has been affected” (Bridge Strength = 0.783) were the two most prominent bridge nodes.ConclusionThis research reveals the core and bridge symptoms in different symptomatic profiles (such as perceived stigma, depression symptoms, and their combination networks), which can be targeted for treatment personalization and aid in diminishing depressive symptoms and perceived stigma among MHD patients.